2015
DOI: 10.1111/bcp.12794
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic and pharmacodynamic interaction of clopidogrel and cilostazol in relation to CYP2C19 and CYP3A5 genotypes

Abstract: AIMThe primary objective of the present study was to evaluate the pharmacokinetic and pharmacodynamic interactions between clopidogrel and cilostazol in relation to the CYP2C19 and CYP3A5 genotypes. METHODSIn a randomized, three-way crossover study, 27 healthy subjects were administered clopidogrel (300 mg), cilostazol (100 mg) or clopidogrel + cilostazol orally. Plasma concentrations of clopidogrel, cilostazol and their active metabolites (clopidogrel thiol metabolite, 3,4-dehydrocilostazol and 4″-trans-hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Adjunctive Cilostazol Versus High Maintenance-Dose Clopidogrel in Acute Myocardial Infarction [AMI] Patients According to CYP2C19 Polymorphism) trial also showed that adjunctive cilostazol therapy significantly diminished the rate of HTPR in AMI patients with CYP2C19 LoF variants [23]. Therefore, DAPT plus cilostazol may benefit those patients who are CYP2C19 poor metabolizers [14]. However, in the present work, no significant differences were found between wild type and carriers of CYP2C19*2 with regard to platelet reactivity in PAD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adjunctive Cilostazol Versus High Maintenance-Dose Clopidogrel in Acute Myocardial Infarction [AMI] Patients According to CYP2C19 Polymorphism) trial also showed that adjunctive cilostazol therapy significantly diminished the rate of HTPR in AMI patients with CYP2C19 LoF variants [23]. Therefore, DAPT plus cilostazol may benefit those patients who are CYP2C19 poor metabolizers [14]. However, in the present work, no significant differences were found between wild type and carriers of CYP2C19*2 with regard to platelet reactivity in PAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we were unable to test a genotype-driven pharmacokinetic interaction between carriers of the CYP2C19*2 and CYP3A5*3 variants among Hispanic PAD patients on cilostazol plus clopidogrel. A previous study suggested that cilostazol might overcome clopidogrel resistance caused by CYP2C19 poor metabolizers, but only in subjects with the CYP3A5*3/*3 genotype [14]. It is postulated that patients with a CYP3A5*3/*3 genotype have decreased clearance of the active metabolite of clopidogrel, in effect compensating for the decreased formation of the active metabolite in patients carrying CYP2C19*2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen sets of clinic pharmacokinetic data of CLOP and CLOP-AM following oral dose of CLOP to healthy subjects were included in the study. The plasma concentration-time profiles ( Figure 2 ) and corresponding pharmacokinetic parameters of CLOP and CLOP-AM following different doses of CLOP ( Table 4 ) to healthy subjects were predicted using developed model and compared with reported data ( Brandt et al, 2007 ; Kim et al, 2008 ; Umemura et al, 2008 ; Simon et al, 2011 ; Kelly et al, 2012 ; Oh et al, 2014 ; Pedersen et al, 2014 ; Holmberg et al, 2014 ; Horenstein et al, 2014 ; Kim et al, 2014 ; Kobayashi et al, 2015 ; Kim et al, 2016 ; Umemura and Iwaki, 2016 ; Song et al, 2018 ; Zhang et al, 2020 ). The results showed that most of the predicted concentrations of CLOP-AM fell within 0.5∼2.0 folds of the observed concentrations ( Figure 2F ), while the predictions for pharmacokinetics of CLOP-AM after multiple doses were deviated from the clinical reports ( Figures 2C , E ).…”
Section: Resultsmentioning
confidence: 99%
“…For pharmacokinetic validation, the variances of V max,CYP2C19 , CL int,CES1 and K t,i with standard deviation of intra-individual error were estimated using four sets of observed CLOP-AM plasma concentration-time profiles in healthy subjects ( Kobayashi et al, 2015 ; Umemura and Iwaki, 2016 ; Song et al, 2018 ; Zhang et al, 2020 ). For pharmacodynamic validation, the variances of V max,CYP2C19 , CL int,CES1 , K t,i , and k irre were also estimated with three sets of reported IPA-time profiles in healthy individuals ( Kim et al, 2008 ; Kobayashi et al, 2015 ; Kim et al, 2016 ). Then, the simulation and verification of the established population model, which based on 1,000 simulations, were performed on Pheonix WinNonlin (Version 8.1, Pharsight Cooperation, st. Louis, Missouri).…”
Section: Methodsmentioning
confidence: 99%